Atypical Femoral Fractures: A Teaching Perspective. Issue 2 (May 2015) - Khan, Aliya A.; Leslie, William D.; Lentle, Brian; Iles, Sian; Kaiser, Stephanie M.; Frame, Heather; Burrell, Steven; Cheung, Angela M.
This article provides an overview of atypical femoral fractures with a highlight on their radiographic findings. Potent antiresorptive agents such as bisphosphonates or denosumab have been associated with the development of such fractures. However, at this time, a causal association has not been conclusively established. Atypical femoral fractures are insufficiency fractures, which frequently present with bone pain. Early identification of characteristic radiographic features and withdrawal of antiresorptive therapy may prevent the development of completed atypical femoral fractures.